The use of Kristang in the Portuguese settlement of Malacca - Nunes, Mario Pinharanda (Journal of Modern Languages, 2017)
The writer's contact with members of the community over the last few years has prompted this investigation into the use of Kristang and the chances of its survival. As interest has been expressed by certain parties to aid the community, the data collected in this study could be used in plans to promote the survival of the community and language. The data was obtained from a survey undertaken to collect information on the use of Kristang in the Settlement. However. since only a quarter of the population in the Portuguese Settlement participated in the survey, this study can only offer a general picture of the use and survival of Kristang in the Settlement.